Investigating the acute cognitive effects of dietary compounds using fNIRS: methodological limitations and perspectives for research targeting healthy adults - Zahar, Sélima; Van de Ville, Dimitri; Hudry, Julie (Frontiers in Human Neuroscience, 2024)
The brain’s response to cognitive demands hinges on sufficient blood flow, with changes in brain hemodynamics serving as a reflection of this process. Certain bioactive compounds found in our diet, such as caffeine, polyphenols, and nitrate, can acutely impact brain hemodynamics through diverse neural, vasoactive, and metabolic mechanisms. Functional Near-Infrared Spectroscopy (fNIRS) offers a non-invasive and real-time method to investigate these effects. Despite their potential, fNIRS studies investigating the acute impacts of bioactive compounds on cognition face methodological gaps, especially in controlling confounding factors. Given the impact of these confounding effects, which can be significant due to the relatively limited sample size of such studies, there is a need to refine the methodologies employed. This review proposes recommendations to enhance current methodologies in the research field, focusing on key aspects of the data collection phase, including research design, experimental paradigms, and participant demographics, and their integration into the analysis phase. Ultimately, it seeks to advance our understanding of the effects of bioactive compounds on cognitive functions to contribute to the development of targeted nutritional interventions for improved brain health.